Metode Pembelajaran Bahasa Arab Pada Anak Usia Dini - Budi Santoso Wibowo; Fakhriyah Annisa Afroo; Putri Dea Cantika (Journal on Education, 2024)
Early childhood has a good memory. They can learn, understand, and use language well because they get language experience directly from their surrounding environment. This language experience helps early childhood learners understand and use language well. One of the most important languages to teach to young children is Arabic. In order for learning to be effective and for early childhood to be able to understand the material taught well, a learning method that suits their needs and abilities is necessary. This research is a literature research. Library research is an argumentative disclosure of data sources in the form of a study. The results of this study reveal the methods that can be used in learning in early childhood, namely: (1) direct method, (2) singing method, and (3) educational game method.